UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK MENGGUNAKAN KARTU HURUF PADA KELOMPOK B: Kemampuan Membaca permulaan, media kartu huruf - Mogi, Martina; Meka, Marsianus; Ita, Efrida (Jurnal Citra Pendidikan Anak, 2022)
Abstract This study aims to improve children’s initial reading skills in group B at Cahaya Baru, Malanuza Satu village, Golewa district, Ngada District for the 2021/2022 academic year by using letter cards as media. The type of research is classroom action research. The implementation of this research activity uses the Kemmis and Mc. Taggart (Kusuma and Dwigtama, 2010 :21), with the following research steps: plan, act, observer and reflect. Subjects in the study of group B children aged 5- 6 years at TKK Cahaya Baru Malanuza Satu village, consisten of 12 children. The object of this study is language ability (start reading). Data collection methods using observation and documentation methods. Any activities carried out, is an activity related to the ability to read the beginning is to pronounce the alphabet A- Z, recognize vowels and consonants, connect letters into simple words, and imitating A- Z writing. The increase can be proven by the percentage gain which reaches 75% in cycle II. This through the media of letter cards, the initial reading ability of group B children in TKK Cahaya Baru has increased. Therfore teachers are advised to prepare more appropriate learning media to attract students’ interesy in carrying out learning activities.